Studi Komperatif Pemahaman Kedudukan Wanita Dalam Tafsir Klasik Dan Modern - Rohmah, Kamila Sofiana; Hudan, Sabila Tursina; Khoirunnisa , Fajar; Nurhuda, Abid; Bin Engku Ab Rahman, Engku Shahrulerizal (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This study analyzes the comparative understanding of the position of women in classical and modern interpretations, as well as the social implications of these differences in interpretation in the context of contemporary Muslim society. The research method used is qualitative with a literature study approach, involving analysis of classical interpretation books. The results of the study indicate that classical interpretations tend to interpret verses about women textually and normatively, focusing on domestic roles and household relations, while modern interpretations use a contextual and socio-historical approach that emphasizes gender equality and relevance to social reality. The conclusion of this study reveals that the development of interpretation from classical to modern reflects a paradigm shift from a literal understanding to a holistic understanding that is adaptive to social change. This study contributes to an inclusive Islamic discourse and supports gender justice in Islam